Taxonomic reappraisal of a morphologically complex group of “manacás” and “quaresmeiras” (Pleroma, Melastomataceae): phenological, morphological, and in vivo evidence of hidden diversity - Meyer, Fabrício Schmitz; Lubow, Sacha (Phytotaxa, 2026)
We present a taxonomic reassessment of a morphologically complex group of “manacás” and “quaresmeiras”, characterized by strigose branches covered with appressed trichomes and flower buds subtended by six cucullate bracteoles. These species belong to a group of Pleroma (Melastomataceae) endemic to the Brazilian Atlantic Forest and widely cultivated as ornamental trees in urban landscaping. Based on morphological analyses, herbarium surveys, phenological data, and in vivo observations, we demonstrate that the current taxonomic interpretation—treating P. pulchrum as a synonym of P. raddianum—obscures a distinct taxonomic entity. By reinstating P. pulchrum and redefining P. raddianum, we clarify identification limits using consistent morphological characters. Discontinuities in leaf venation, bracteole size, and floral characters—particularly differences in the size, shape, and indumentum of floral parts—as well as fruit size delimit three species—P. pulchrum, P. raddianum, and P. sellowianum—which are often confused due to their overall morphological similarity. Most plants propagated ornamentally, frequently referred to as Tibouchina mutabilis “Nana” (an illegitimate name), correspond to P. raddianum and differ from native populations by subtle morphological differences, including leaf venation, petal colour pattern, and merosity. These differences are likely related to local genetic characteristics and the origin of these progenies, which are commonly propagated by cuttings, have resulted in clonal plants with fixed and uniform morphology. The three species, P. pulchrum, P. raddianum, and P. sellowianum, exhibit largely non-overlapping flowering peaks—summer, early autumn, and winter, respectively—and partially contiguous distributions, suggesting possible zones of secondary contact. We provide concise descriptions of P. pulchrum, P. raddianum, and P. sellowianum, along with an identification key for the species group, characterized by solitary flowers and petals that change colour during senescence. Distribution maps and comparative illustrations are also presented. This treatment improves species recognition and refines the current understanding of Pleroma diversity in the Atlantic Forest.